Ivashkevych L. Difficulties in the translation of modern German job titles into Ukrainian - Ivashkevych L. (Philological Treatises, 2020)
The article deals with the differences in the systems of modern German and Ukrainian job titles and the difficulties those differences cause while translating. It holds a diachronic and synchronic comparison of the German and Ukrainian job classifier and two of their specific areas. The characteristic tendencies of the modern German profession titles are defined, and their representation in the Ukrainian nominations is clarified. Basing on the received data and numerous examples, we show the difference in the gender visualization of the professional titles of the both languages. Besides differences in the extent of their generalization, and the character of borrowings in comparison with other languages are revealed. We recommend how the discovered differences in the job title systems can be considered in translation depending on the extralinguistic situation.